A részmunkaidős foglalkoztatás tendenciái és terjedésének tényezői az Európai Unióban és magyarországon - Antal Seres (Hungarian Academy of Sciences, Institute of Economics, 2010)
– In the employment increase of 12 million of the European Union the number of part time employees accounted for nearly 6 million between 2000 and 2006. A great number of countries try to support the distribution of part-time employment in order to raise or maintain the level of employment and to organise the work and working time more efficiently and intensively. Hungary with its low level of part-time employment is among the last Member States of the European Union, therefore, on the one hand this flexible type of employment can be considered as an unused reserve of workforce management and on the other hand, the low level of employment is due to the narrow size distribution of part-time employment. By examining the factors influencing the part-time employment this publication aims to facilitate the clarification of the role of part-time employment; and furthermore, to increase its weight in the Hungarian economy and employment.
Keywords: J22; 330; part-time; employment; fluctuation of economic activity; modernization of the working organisation; employment policy; system of social partnership; Teilzeitarbeit; Arbeitsmarktpolitik; EU-Staaten; Ungarn